2013
DOI: 10.1111/1556-4029.12106
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Fatalities in New Mexico: Medical Examiner‐Investigated Cases, 20002010

Abstract: To better understand risk factors and populations at risk of childhood fatalities, a review of all records of childhood deaths (≤19 years) between 2000 and 2010 from New Mexico's statewide medical examiner was conducted. Annually, 313-383 childhood deaths were investigated (3820 total). Males and American Indians were overrepresented (62% and 20.4% of deaths, respectively). The most common manner of death was natural (44.8%), followed by accidental (31.4%), homicide (8.8%), suicide (8.8%), and undetermined (4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…According to Statistics SA, [4] the majority of infants in SA die from natural disease processes. Lathrop [16] indicated that natural causes were the most common cause of death among all age groups, accounting for 44.8% of all deaths, with 77% of these in infants. In 86 (9%) cases no cause of death could be ascertained at autopsy alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Statistics SA, [4] the majority of infants in SA die from natural disease processes. Lathrop [16] indicated that natural causes were the most common cause of death among all age groups, accounting for 44.8% of all deaths, with 77% of these in infants. In 86 (9%) cases no cause of death could be ascertained at autopsy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Lathrop [16] indicated that 'complete medicolegal investigation of childhood fatalities is needed to provide public health agencies with adequate data to evaluate and prevent childhood deaths' . This author also suggests reporting the causes of death separately for each year of life rather than in groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diğer çalışmalar ile benzer olarak bu çalışmada da kaza sonucu ölümlerde çocukların çoğunun (%65,7) erkek olduğu saptanmıştır (8,10,12,(15)(16)(17). Bunun kız çocuklarına oranla erkeklerin daha hareketli ve meraklı bir yapıya sahip olmalarına ve ayrıca ev dışında daha fazla zaman geçirmelerine bağlı olduğu düşünülmüştür.…”
Section: Tablo 1 öLümlerin Orijininin Yaş Grupları Ve Cinsiyete Göreunclassified
“…Diğer çalışmalarda da kaza sonucu ölümlerin en fazla trafik kazalarına bağlı olduğu, sıralama değişmekle birlikte trafik kazalarını düşme, suda boğulma ve diğer asfiksiler, zehirlenme ile yanıkların izlediği belirtilmiştir (5,6,(10)(11)(12)(13)(14)(15)(16)(17). Bu çalışmada ayrıca trafik kazalarının sırasıyla en çok 5-9 ve 10-14 yaş gruplarında görüldüğü, 1-4 yaş grubunda ev kazalarının trafik kazalarından daha fazla olduğu tespit edilmiştir.…”
Section: Tablo 1 öLümlerin Orijininin Yaş Grupları Ve Cinsiyete Göreunclassified